Detection of Strawberry vein banding virus (SVBV) and Identification of Viruliferous Insects Associated with Strawberry Plants (Fragaria sp.) in Bali - I Putu Sudiarta; Gusti Ngurah Alit Susanta Wirya; Dewa Gede Wiryangga Selangga; Made Getas Pudak Wangi (Jurnal Perlindungan Tanaman Indonesia, 2021)
Plant pests and diseases cause decreases in strawberry yield in Bali, including plant viruses. Strawberry vein banding virus (SVBV) is a virus that infects strawberry plants and is transmitted by insects. However, studies about this disease in Bali are still limited. This study aimed to detect SVBV within insect bodies and determine the insect species of its vector. Methods used included (1) sampling; (2) detection of SVBV from insect bodies using primers (SVBV F/SVBV R) and PCR; and (3) molecular identification of viruliferous insect with primers (LCO 1490 F/HCO 2198 R) using PCR and sequencing analysis. This study successfully detected SVBV DNA in an insect from three insect families associated with strawberry plants in Pancasari Village, Buleleng Regency, Bali. Results from the nucleotide sequences analysis in SVBV viruliferous insects indicate that the insect was Myzus persicae.